Microbial profile and risk factors of central venous catheter associated blood stream infections in Tertiary Care Hospital, Amritsar - Loveena Oberoi; Pallavi Pallavi; Veena Chatrath; Pushpa Devi (International Journal of Medical Research and Review, 2016)
Introduction: Central venous catheter (CVC) related blood stream infections are associated with serious infectious complications resulting in significant morbidity, increased duration of hospitalization and added medical cost.Aim: The study was done to determine the incidence of central venous catheter related infections, their antimicrobial sensitivity pattern, biofilm production and associated risk factors in hospitalized patients.Material and Method: Catheter tip culture & blood cultures of 143 patients with indwelling central venous catheters were processed.Result: Out of 143 specimens, catheter tip colonization was observed in 45 samples, while 14 were both catheter tip as well as blood culture positive hence included ascatheter related blood stream infections (CRBSI). CRBSI was found significantly associated with increased duration of catheterization, increased number of attempts and placement of CVC in internal jugular vein. Most common isolated organisms were Klebsiella pneumoniae followed by Coagulase negative Staphylococcus, Staphylococcus aureus and Pseudomonas aerguinosa in CRBSI as well as in CVC colonization. Majority of them were resistant to Gentamicin, Ciprofloxacin, Ceftiazidime and Ceftrixone. Biofilm production was determined by tissue culture plate method and was found to be maximum seen in Klebsiella spp.Conclusion: Incidence of CRBSI was 9.79% and of CVC colonization was 34.26%. Rate of CRBSI was 8.53 per 1000 CVC days. Klebsiella pneumoniae was most common isolate and predominant biofilm producer and was found to be multidrug resistant to Gentamicin, Ciprofloxacin, Ceftiazidime.